The Effects of 8 Weeks of FIFA11+ Warm-Up Program on Timing and Electromyography Activity of Knee Muscles to Prevent the ACL Injury - Vahid Ghasemi paeendehi; Sadroddin Shojaeddin; Esmail Ebrahimi-Tekamejani; Amir Letafatkar; Mansoor Eslami (Sport Sciences and Health Research)
The aim of this study was to investigate the effect of FIFA11+ injury prevention program on the timing and electrical activity of knee related muscles in young male soccer players. EMG data during single-limb drop landing of 24 young male soccer players (12 control and 12 experimental) were collected in pretest and posttest. After 8 weeks of training in experimental group, analysis of variance with repeated measures, independent sample t test and paired sample t test were used for statistical analysis. The results showed that vastus medialis (VM), medial hamstring (MH) and medial gastrocnemius (MG) activities increased while the vastus lateralis (VL), lateral hamstring (LH), rectus femuris (RF) and lateral gastrocnemius (LG) activities decreased after the training. FIFA11+ training decreased the timing of RF, VL, LH and LG whereas it increased the timing of VM, MH and MG. The study found out that FIFA11+ program can improve the neuromuscular characteristics of lower extremities in young soccer players, can potentially reduce the risk of ACL injury during landing and lead to ACL optimal control.